The relationship between peak height velocity and physical performance in youth soccer players - Philippaerts, R. M.; Vaeyens, R.; Janssens, M.; van Renterghem, B.; Matthys, D.; Craen, R.; Bourgois, J.; Vrijens, J.; Beunen, G.; Malina, R. M. (Journal of Sports Sciences, 2006)
Longitudinal changes in height, weight and physical performance were studied in 33 Flemish male youth soccer players from the Ghent Youth Soccer Project. The players' ages at the start of the study ranged from 10.4 to 13.7 years, with a mean age of 12.2 ± 0.7 years. Longitudinal changes were studied over a 5 year period. Peak height velocity and peak weight velocity were determined using non-smoothed polynomials. The estimations of peak height velocity, peak weight velocity and age at peak height velocity were 9.7 ± 1.5 cm · year-1, 8.4 ± 3.0 kg · year-1 and 13.8 ± 0.8 years, respectively. Peak weight velocity occurred, on average, at the same age as peak height velocity. Balance, speed of limb movement, trunk strength, upper-body muscular endurance, explosive strength, running speed and agility, cardiorespiratory endurance and anaerobic capacity showed peak development at peak height velocity. A plateau in the velocity curves was observed after peak height velocity for upper-body muscular endurance, explosive strength and running speed. Flexibility exhibited peak development during the tear after peak height velocity. Trainers and coaches should be aware of the individual characteristics of the adolescent growth spurt and the training load should also be individualized at this time.